Multiple phytoplankton community responses to environmental change in a temperate coastal system: A trait-based approach - Breton, Elsa; Goberville, Eric; Sautour, Benoit; Ouadi, Anis; Skouroliakou, Dimitra-Ioli; Seuront, Laurent; Beaugrand, Gregory; Kléparski, Loïck; Crouvoisier, Muriel; Pecqueur, David; Salmeron, Christophe; Cauvin, Arnaud; et al. (Frontiers in Marine Science, 2022)
The effect of environmental change in structuring the phytoplankton communities of the coastal waters of the Eastern English Channel was investigated by applying a trait-based approach on two decades (1996-2019) of monitoring on diatoms and Phaeocystis. We show that phytoplankton species richness in an unbalanced nutrient supply context was influenced by wind-driven processes, ecological specialization for dissolved inorganic phosphorous, temporal niche differentiation, and a competition-defense and/or a growth-defense trade-off, a coexistence mechanism where weak competitors (i.e., slower growing) are better protected against predation. Under the influence of both environmental perturbations (e.g., wind-driven processes, freshwater influence, unbalanced nutrient levels) and biotic interactions (e.g., competition, predation, facilitation), phytoplankton species exhibited specific survival strategies such as investment on growth, adaptation and tolerance of species to environmental stresses, silicification and resource specialization. These strategies have led to more speciose communities, higher productivity, functional redundancy and stability in the last decade. Our results revealed that the unbalanced nutrient reduction facilitated Phaeocystis blooms and that anthropogenic climate warming may threaten the diatom communities of the eastern English Channel in a near future. Our results provide strong support for biogeographical historical and niche-based processes in structuring the phytoplankton community in this temperate region. The variety of species responses that we characterized in this region may help to better understand future changes in pelagic ecosystems, and can serve as a basis to consider functional approaches for future ecosystem management.